Condiciones de trabajo y satisfacción laboral del personal de salud de Trujillo de salud de centro quirúrgico - Hospital Regional Docente de Trujillo - López Díaz de Cabrera, Alicia Margarita (2019)
The present research study is of a quantitative, descriptive-correlational and cross-sectional type. It was carried out with the health personnel of the surgical center during the months of January and February 2016, whose objective was to determine the relationship that exists between working conditions and the level of job satisfaction. The sample population consisted of 51 people among doctors, nurses and nursing technicians who met the established inclusion criteria. The information was obtained through the instruments: Assessment of working conditions and for job satisfaction the Font Roja Questionnaire which are valid and validated. The results obtained were tabulated and presented in simple and double entry statistical tables. The information obtained was processed using the statistical program IBM, SPSS STATISTIC 23. From the results it is concluded that there are acceptable work conditions, the same ones that have a significant relationship with the average level of job satisfaction